Housing Resilience and the Informal City - Jones, Paul (Journal of Regional and City Planning, 2017)
Abstract. Central to managing urban growth in the new millennium is understanding the role and nature of the resilience shown by residents and communities in growing towns and cities, and especially in what can be termed the informal city. Urban resilience is defined as the ability of cities to manage and adapt to change, and includes robustness, mitigation and adjustment at all levels. On the other hand, the informal city is about spaces, places and communities where residents adapt to the circumstances at hand using locally based rules, processes and governance. These actions are generally âoutsideâ the structures and processes that guide order and control in the formally planned city. Using the kampung locality of Tamansari in Bandung, Indonesia, as a case study, an analysis of housing resilience and understanding of the local dynamics of housing adaptation in Tamansari was undertaken by assessing four elements, namely, the collective resilience at the Tamansari level, vertical and horizontal housing adaptations, and changes to functionality and space in alleyways and public areas. Five key findings are identified: (i) there is commonality in what residents are seeking, namely, additional living space, modified access ways, privacy, and access to light and air circulation, (ii) a variety of construction methods and materials are utilized, (iii) the process of transformation is âstep by stepâ and incremental, (iii) notions of physical private/public boundaries are fluid, reflecting their flexibility and ability to be locally negotiated and contested, and (v) housing and wider circulation and activity spaces are defined by their multi-functionality. In this setting, legitimization of the informal city by the State is critical as informal settlements play an important role for residents to express and develop their skills of resiliency which may not be acceptable and or tolerated in other parts of the city.Keywords. housing, informal city, resilience.Abstrak. Hal utama dalam pengelolaan pertumbuhan perkotaan di milenium baru ini adalah memahami peran dan ketahanan yang ditunjukkan oleh penduduk dan komunitas di kota-kota, dan terutama pada kota yang dapat disebut sebagai kota informal. Ketahanan perkotaan didefinisikan sebagai kemampuan kota untuk mengelola dan menyesuaikan diri terhadap perubahan, yang mencakup ketahanan, mitigasi dan penyesuaian di semua tingkat. Di sisi lain, kota informal adalah tentang ruang, tempat dan komunitas tempat penduduk beradaptasi pada keadaan yang ada dengan menggunakan peraturan, proses, dan tata kelola setempat. Tindakan ini pada umumnya terjadi di luar struktur dan proses yang memandu keteraturan dan pengendalian di kota yang direncanakan secara formal. Dengan menggunakan kampung Tamansari di Bandung, Indonesia, sebagai studi kasus, analisis ketahanan perumahan dan pemahaman dinamika adaptasi perumahan di Tamansari dilakukan dengan menilai empat elemen, yaitu ketahanan kolektif di tingkat Tamansari, adaptasi perumahan vertikal dan horisontal, serta perubahan fungsi dan ruang di lorong-lorong dan tempat umum. Lima temuan utama telah diidentifikasi: (i) ada kesamaan dalam apa yang dicari penduduk, yaitu ruang hidup tambahan, perubahan jalan akses, privasi, dan akses terhadap sirkulasi cahaya dan udara, (ii) menggunakan berbagai metode dan bahan konstruksi, (iii) proses transformasi terjadi secara bertahap, sedikit demi sedikit, (iii) pengertian batas fisik pribadi/publik tidak pasti, mencerminkan fleksibilitas dan kemampuan mereka untuk dinegosiasikan dan diperebutkan secara lokal, serta (v) perumahan dan sirkulasi serta ruang aktivitas yang lebih luas yang didefinisikan oleh multifungsinya. Pada keadaan ini, legitimasi kota informal oleh negara sangat penting karena permukiman informal memainkan peran penting bagi warga untuk mengekspresikan dan mengembangkan keterampilan mereka mengenai ketahanan yang mungkin tidak dapat diterima dan atau ditolerir di bagian kota yang lain.Kata kunci. Perumahan, kota informal, ketahanan.